Surgical treatment of ventricular septal defect in infancy. Primary repair versus banding of pulmonary artery and later repair. Issue 2 (February 1979) - McNicholas, K; de Leval, M; Stark, J; Taylor, J F; Macartney, F J
Abstract : Results of primary closure of ventricular septal defects are compared with those of two-stage repair, with banding of the pulmonary artery followed by debanding and closure. Apart from the high incidence of unsatisfactory results after banding and a significant morbidity with the two-stage approach, the mortality for primary repair (2.4%) is considerably lower than that achieved with the staged repair (19.3%). Primary repair of ventricular septal defect is advocated for infants resistant to maximal medical treatment. A more flexible policy is adopted for patients with multiple ventricular septal defects and those with associated anomalies.